The contribution of the intestinal microbiome to immune recovery after HCT - Wolfe, Alex E.; Markey, Kate A. (Frontiers in Immunology, 2022)
Allogenic hematopoietic stem-cell transplantation (allo-HCT) is a curative-intent immunotherapy for high-risk hematological malignancies and immune deficiencies. Allo-HCT carries a high risk of treatment-related mortality (TRM), largely due to infection or graft-versus-host disease (GVHD). Robust immune recovery is essential for optimal patient outcomes, given the immunologic graft-versus-leukemia effect prevents relapse, and functional innate and adaptive immunity are both needed for the prevention and control of infection. Most simply, we measure immune recovery by enumerating donor lymphocyte subsets in circulation. In functional terms, ideal immune recovery is more difficult to define, and current lab techniques are limited to the measurement of specific vaccine-responses or mitogens ex vivo. Clinically, poor immune function manifests as problematic infection with viral, bacterial and fungal organisms. Furthermore, the ideal recovering immune system is capable of exerting graft-versus-tumor effects to prevent relapse, and does not induce graft-versus-host disease. Large clinical observational studies have linked loss of diversity within the gut microbiome with adverse transplant outcomes including decreased overall survival and increased acute and chronic GVHD. Furthermore, the correlation between intestinal microbial communities and numeric lymphocyte recovery has now been reported using a number of approaches. Large sets of clinically available white blood cell count data, clinical flow cytometry of lymphocyte subsets and bespoke flow cytometry analyses designed to capture microbiota-specific T cells (e.g. Mucosal-associated invariant T cells, subsets of the gd T cells) have all been leveraged in an attempt to understand links between the microbiota and the recovering immune system in HCT patients. Additionally, preclinical studies suggest an immunomodulatory role for bacterial metabolites (including butyrate, secondary bile acids, and indole derivatives from tryptophan metabolism) in transplant outcomes, though further studies are needed to unravel mechanisms relevant to the post-HCT setting. An understanding of mechanistic relationships between the intestinal microbiome and post-transplant outcomes is necessary for reduction of risk associated with transplant, to inform prophylactic procedures, and ensure optimal immune reconstitution without alloreactivity. Here, we summarize the current understanding of the complex relationship between bacterial communities, their individual members, and the metabolites they produce with immune function in both the allo-HCT and steady-state setting.